The effects of high skilled immigration in a dual labour market with union wage setting and fiscal redistribution - Moritz Bonn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
We study the effects of high skilled immigration on employment and net income in the receiving economy where the market for low skilled labour is distorted by union wage setting and a redistributive unemployment benefit scheme. Based on the empirical fact that high and low skilled workers are close albeit imperfect substitutes, we show that high skilled immigration can either be beneficial or harmful, both in terms of employment and net income. More precisely, we conclude that a Pareto improvement can be achieved if the unemployment benefit level remains unaffected by high skilled immigration whereas an overall loss in net income cannot be ruled out if we suggest unemployment benefits to be funded by an exogenous egalitarian tax rate.
Keywords: F22; H53; J51; J61; 330; immigration; imperfect labour markets; fiscal redistribution; Einwanderung; Hochqualifizierte Arbeitskräfte; Beschäftigungseffekt; Einkommen; Lohnpolitik; Ungelernte Arbeitskräfte; Arbeitslosenversicherung; Einkommensumverteilung; Theorie